Multidisciplinary approach in the treatment of subgingivally fractured anterior teeth - KÖSE, KEMAL NACİ (WILEY, 2008)
With the advances in adhesive technology, dentists have gained great popularity with their esthetics treatment options. The enamel and partially dentin adhesive systems have proved their potential effect. This study presents the multidisciplinary approach in the treatment of subgingivally fractured anterior teeth. Empress II crowns were cemented entirely on the prepared root portion of a left maxillary lateral incisor and canine after orthodontic eruption. The clinical results after 2 years were successful.
Keywords: FORCED ERUPTION; EXTRUSION